Giải PT và HPT:
1)\(\left\{{}\begin{matrix}xy+x+y=3\\\frac{1}{x^2+2x}+\frac{1}{y^2+2y}=\frac{2}{3}\end{matrix}\right.\)
2)\(\left(\sqrt{x+4}-2\right)\left(\sqrt{4-x}+2\right)=2x\)
3)\(\left\{{}\begin{matrix}xy\left(x+y\right)=2\\9xy\left(3x-y\right)+6=26x^3-2y^3\end{matrix}\right.\)
4)\(\left\{{}\begin{matrix}x^2-2xy+x-2y+3=0\\y^2-x^2+2xy+2x-2=0\end{matrix}\right.\)
giải hpt:
1,\(\left\{{}\begin{matrix}x^2y^2-2x+y^2=0\\2x^2-4x+3+y^3=0\end{matrix}\right.\)
2. \(\left\{{}\begin{matrix}\left(x^2-xy\right)\left(xy-y^2\right)=25\\\sqrt{x^2-xy}+\sqrt{xy-y^2}=3\left(x-y\right)\end{matrix}\right.\)
giải HPT
a) \(\left\{{}\begin{matrix}\left(x+3\right)\left(y-5\right)=xy\\\left(2x-y\right)\left(y+15\right)=2xy\end{matrix}\right.\)
b) \(\left\{{}\begin{matrix}\sqrt{4x}-3y+4z^2=-2\\\sqrt{3x}+2y-3z^2=1\\-3\sqrt{x}+y+2z^2=4\end{matrix}\right.\)
\(\left\{{}\begin{matrix}x^3y\left(1+y\right)+x^2y^2\left(2+y\right)+xy^3=30\\x^2y+x\left(1+y+y^2\right)+y=11\end{matrix}\right.\)
giải hpt: a) \(\left\{{}\begin{matrix}x^2+y^2+1=2\left(xy-x+y\right)\\x^3+3y^2+5x-12=\left(12-y\right)\sqrt{3-x}\end{matrix}\right.\)
b) \(\left\{{}\begin{matrix}x+\sqrt{x^2+2x+2}=\sqrt{y^2+1}-y-1\\x^3-\left(3x^2+2y^2-6\right)\sqrt{2x^2-y^2-2}=0\end{matrix}\right.\)
Giải hệ phương trình:
\(a,\left\{{}\begin{matrix}2x^3+x^2y+2x^2+xy+6=0\\x^2+3x+y=1\end{matrix}\right.\)
\(b,\left\{{}\begin{matrix}x^2=\left(2-y\right)\left(2+y\right)\\2x^3=\left(x+y\right)\left(4-xy\right)\end{matrix}\right.\)
\(c,\left\{{}\begin{matrix}\sqrt[3]{x+2y}=4-x-y\\\sqrt[3]{x+6}+\sqrt{2y}=2\end{matrix}\right.\)
Giải hpt: 1, \(\left\{{}\begin{matrix}x^3-y^3=3y^2+9\\x^2+y^2=x-4y\end{matrix}\right.\)
2,\(\left\{{}\begin{matrix}x^2+2xy+2y^2+3x=0\\xy+y^2+3y+1=0\end{matrix}\right.\)
Giải hpt:
a, \(\left\{{}\begin{matrix}9y^3\left(3x^3-1\right)=-125\\45x^2y+75x=6y^2\end{matrix}\right.\)
b, \(\left\{{}\begin{matrix}3\left(x^2+y^2\right)+\dfrac{1}{\left(x-y\right)^2}=2\left(10-xy\right)\\2x+\dfrac{1}{x-y}=5\end{matrix}\right.\)
a. \(\left\{{}\begin{matrix}x^2-3x+2y=2\\2x^2+y-x=3\end{matrix}\right.\)
b.\(\left\{{}\begin{matrix}x^2+y^2+xy-3y=4\\2x-3y+xy=3\end{matrix}\right.\)
c.\(\left\{{}\begin{matrix}2x^2=y+\frac{1}{y}\\2y^2=x+\frac{1}{x}\end{matrix}\right.\)
d.\(\left\{{}\begin{matrix}x^2-2y^2-xy-2x+7y-3=0\\x^2+y^2-x+y=0\end{matrix}\right.\)